Hierarchical nanocomposite composed of layered V2O5/PEDOT/MnO2 nanosheets for high-performance asymmetric supercapacitors. (March 2015) - Guo, Chun Xian; Yilmaz, Gamze; Chen, Shucheng; Chen, Shaofeng; Lu, Xianmao
Abstract: We present here a tandem redox reaction strategy for building layered V2 O5 (LVO), conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT), and layered MnO2 (LMO) into a sandwich structure LVO\PEDOT\LMO. The fabrication process consists of two redox reactions: (i) the oxidizing polymerization of PEDOT on LVO nanosheets to form a conformal coating (LVO\PEDOT); and (ii) the reduction of KMnO4 by PEDOT to generate LMO nanoplates that stacked onto the LVO\PEDOT (LVO\PEDOT\LMO). This approach to the fabrication of a complex structure eliminates the use of any extra toxic oxidizing/reducing agents. Using LVO aerogel as the starting material, the total reaction time can be as short as 10 min. Asymmetric supercapacitors built from LVO\PEDOT\LMO cathode and active carbon (AC) anode (LVO\PEDOT\LMO||AC) using Na2 SO4 aqueous electrolyte showed an energy density of 39.2 Wh kg −1 (based on active materials), which is among the highest reported for supercapacitors with neutral aqueous electrolytes. The LVO\PEDOT\LMO||AC supercapacitors also offered high rate capability (21.7 Wh kg −1 at 2.2 kW kg −1 ) and good cycle stability (93.5% capacitance retention after 3000 cycles). These results demonstrate that the green tandem redox reaction strategy is promising for the development of complex nanocomposite materials for advanced energy storage. Graphical abstract: Highlights: Layered V2O5/PEDOT/MnO2 nanosheets were sandwiched into a hierarchical structure. The fabrication was based on a green and fast tandem redox reaction strategy. Supercapacitors using neutral aqueous electrolyte showed a high energy density of 39.2 Wh kg −1 . High rate capability and good cycle stability were demonstrated.